Evolving concept and popularity of influencers: a literature review - Erini Mutia Yufada; Tigor Nirman Simanjuntak (Jurnal Komunikasi Profesional, 2023)
The growth of the internet use is in line with the swift development of social media. For users, social media is no longer just a place to socialize online, but also as source of various information. The shift in this function has provided great opportunities for influencer activities to influence consumer’s purchase intention through social media. This activity has grown into a lucrative marketing communications industry, making this a very popular phenomenon. This study aims to discover the shift in influencer concept in historical aspect, and asses the condition and potentials of this industry in Indonesia, by using a literature review approach and various secondary data. This research shows the development of the influencer concept from a traditional context to a more modern context, and 2016 was the first moment of serious growth in this industry. It also concludes that this industry has a promising prospect in Indonesia.